Utilização de métodos ativos na transformação de um prédio em um edifício de energia zero: estudo de caso da biblioteca central da Universidade Federal do Pará - ALBUQUERQUE, Bruno Santana de (Universidade Federal do Pará, 2025)
This dissertation proposes an energetic evaluation of a University Building transformation into a Zero Energy Building (ZEB), by using active methods such as Lighting System (LS), Photovoltaic System (PV) and Storage System (SS), and presents its application in the form of a case study. The purpose of this study is to analyze the energy balance between the UFPA Central Library, the implementation of the LS, the PV, the distribution system and the SS, aiming at the load autonomy. Satisfactory results were obtained for different scenarios created by the load variability, according to the university calendar, and the photovoltaic generation intermittency. The proposed LS reduced the building consumption by 44%. Using the PV system generates enough energy to supply most of the building load, however only 53% of this energy benefits the building, the energy surplus supplies other university loads. However, the SS integration allows the building to benefit 77% of the generated energy. Therefore, the proposed systems provide the ZEB concept to the study case building.